Systematic Literatur Review: Psychomotor Assessment In Biology Learning - Nurul Intan Cahyani Intan; Cindy Wulandari; Ulva Widya Astuti; Yaumil Magfirah Armas; Sayyidah Sayyidah (Biology and Biology Education Journal, 2024)
This research uses the Systematic Literature Review (SLR) method to collect, analyze and assess scientific literature relevant to the topic in a structured manner. In this context, SLR is applied to systematically identify literature related to Psychomotor Assessment in Biology Learning. The data source for this research comes from articles in national research journals in the last 10 years, namely 2014 to 2024. The research stages in this literature review consist of 6 stages, namely selecting research topics, literature search, article reduction, article display , discussion, and conclusion. The research results show that psychomotor assessment in various school and subject contexts can be carried out effectively using valid and reliable instruments. Various assessment methods, such as project assessments, simulation tests, and the use of questionnaires, can increase the accuracy of assessments and help teachers understand and develop students' psychomotor skills. However, it should be noted that assessment results may vary depending on the quality of the instruments and methods used, as well as the implementation of the practicum and the level of student involvement in the learning process.